2011
DOI: 10.1039/c0an00919a
|View full text |Cite
|
Sign up to set email alerts
|

Artificial-epitope mapping for CK-MB assay

Abstract: A quantitative method using artificial antibody to detect creatine kinases was developed. Linear epitope sequences were selected based on an artificial-epitope mapping strategy. Nine different MIPs corresponding to the selected peptides were then fabricated on QCM chips. The subtle conformational changes were also recognized by these chips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…A number of papers report assays based upon competitive ligand binding studies . The high sensitivities of assays using either radiolabeled or non‐isotopically labeled studies (fluorescence and chemiluminescence) afford access to events taking place at very‐low concentration regimes that are not generally accessible with chromatographic methods.…”
Section: Applicationsmentioning
confidence: 99%
“…A number of papers report assays based upon competitive ligand binding studies . The high sensitivities of assays using either radiolabeled or non‐isotopically labeled studies (fluorescence and chemiluminescence) afford access to events taking place at very‐low concentration regimes that are not generally accessible with chromatographic methods.…”
Section: Applicationsmentioning
confidence: 99%
“…The HIV PR 85–94 peptide templated HEMIPs were prepared as a co-polymer on a QCM chip using acrylic acid, acrylamide, N -benzylamide and EBAA ( N , N’ -ethylene bisacrylamide), in line with our previous studies [ 22 , 23 , 24 , 25 ]. First, an amino acid cross-linker ( N -Acr- l -Cys-NHBn) 2 was used as a thiol-ene monomer, which enables simple functionalization with binding groups for the polymer’s immobilization of gold chips and an initiator for UV-irradiated photopolymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, an epitope template-based system is simpler and safer for detecting HIV PR and screening its inhibitors. Our studies have shown that an MIP-coated QCM sensor using epitope imprinting significantly strengthens the detection of protective antigens and their segments [ 22 , 23 ]. These results also suggest that functionalized epitope cavities on a QCM surface can effectively catch an oriental antigen.…”
Section: Introductionmentioning
confidence: 99%
“…Tai et al developed a MIP-QCM assay for the detection of creatine kinases [52]. Linear epitope sequences were selected based on an artificial-epitope mapping strategy.…”
Section: Mip-based Quartz Crystal Microbalance Bioassaysmentioning
confidence: 99%